The potential for animal breeding in Africa - Trail, J.C.M. (International Livestock Centre for Africa, 1985)
Presents the current status of animal breeding in Africa and indicates the potential for Development and implementation of breeding programs. Discusses ecological zones, breeding possibilities and productivity of cattle breeds.